Chronic Ethanol (EtOH) Consumption Differentially Alters Gray and White Matter EtOH Methyl 1H Magnetic Resonance Intensity in the Primate Brain. (29th March 2013) - Kroenke, Christopher D.; Flory, Graham S.; Park, Byung; Shaw, Jessica; Rau, Andrew R.; Grant, Kathleen A.
Abstract : Background: In vivo magnetic resonance spectroscopy (MRS) has previously been used to directly monitor brain ethanol (EtOH). It has been proposed that the EtOH methyl 1 H resonance intensity is larger in EtOH‐tolerant individuals than in sensitive individuals. To characterize the relationship between long‐term EtOH exposure and the brain EtOH MRS intensity, we present data from a longitudinal experiment conducted using nonhuman primate subjects. Methods: In vivo MRS was used to measure the gray matter (GM) and white matter (WM) EtOH methyl 1 H MRS intensity in 18 adult male rhesus macaques at 4 time points throughout the course of a chronic drinking experiment. Time points were prior to EtOH drinking, following a 3‐month EtOH induction procedure, and following 6, and 12 subsequent months of 22 h/d of "open access" to EtOH (4% w/v) and water. Results: The EtOH methyl 1 H MRS intensity, which we observed to be independent of age over the range examined, increased with chronic EtOH exposure in GM and WM. In GM, MRS intensity increased from naïve level following the EtOH induction period (90 g/kg cumulative EtOH intake). In WM, MRS intensity was not significantly different from the EtOH‐naïve state until after 6 months of 22‐hour free access (110 to 850 g/kg cumulative intake range). The WM MRS intensity in the EtOH‐naïve state was positively correlated with future drinking, and the increase in WM MRS intensity was negatively correlated with the amount of EtOH consumed throughout the experiment. Conclusions: Chronic exposure to EtOH is associated with brain changes that result in differential increases in EtOH MRS intensity in GM and WM. The EtOH‐naïve WM MRS intensity pattern is consistent with its previously proposed relationship to innate tolerance to the intoxicating effects of EtOH. EtOH‐dependent MRS intensity changes in GM required less EtOH exposure than was necessary to produce changes in WM. Within WM, an unexpected, potentially age dependent, enhanced sensitivity to EtOH in light drinkers relative to heavy drinkers was observed.